An Assessment of Maintainability of an Aspect-Oriented System. (10th February 2013) - Mguni, Kagiso; Ayalew, Yirsaw
Abstract : Software maintenance is an important activity in software development. Some development methodologies such as the object-oriented have contributed in improving maintainability of software. However, crosscutting concerns are still challenges that affect the maintainability of OO software. In this paper, we discuss our case study to assess the extent of maintainability improvement that can be achieved by employing aspect-oriented programming. Aspect-oriented programming (AOP) is a relatively new approach that emphasizes dealing with crosscutting concerns. To demonstrate the maintainability improvement, we refactored a COTS-based system known as OpenBravoPOS using AspectJ and compared its maintainability with the original OO version. We used both structural complexity and concern level metrics. Our results show an improvement of maintainability in the AOP version of OpenBravoPOS.